Prevalence of anemia: A hospital-based diagnostic study - Gargi Jadaun; Esther Pathi; Sayeeda Kharodia; Deepa Pillai; Shibani Sarangi (Wolters Kluwer Medknow Publications, 2024)
Objectives: To determine the prevalence of anemia in female patients and its association with age, nutritional status, body mass index, number of children, intra-oral and extra-oral clinical finding. Materials and Methods: A total of 1000 participants in various age groups were taken as sample, and a pro forma was used to collect data. Hemoglobin was recorded using Sahli's method and categorized according to WHO. Statistical relation between anemia and age, nutritional status, BMI, marital status, intra-oral signs, and extra-oral signs was recorded. Results: A total of 485 out of 1000 patients in total had hemoglobin less than 12 gm%, 247 patients in the age group of 14-30 years, 188 patients in age group of 31-50 years, and 50 patients above 51 years had hemoglobin below 12 gm%; 188 vegetarian patients and 300 in the mixed category had hemoglobin below 12 gm%; 285 patients with BMI less than 18 were anemic; 270 patients without any intra-oral signs, 70 patients with bald tongue, 69 patients with cheilitis, 76 with both bald tongue and cheilitis were anemic; and 140 patients without any extra oral signs and 345 with pallor were anemic. Conclusion: The study concluded that these could be a risk factor for anemia in women, and there is a need to develop strategies for health education.